Is Altered Surfactant Protein Gene Expression in Peripheral Blood Associated with COVID-19 Disease Severity? - Suna Koc; Kamil Cankut Senturk; Sefa Cetinkaya; Guven Yenmis; Hulya Arkan; Mahmut Demirbilek; Pinar Acar; Erhan Arikan; Mehmet Dokur (Diagnostics)
Background/Objectives: Severe COVID-19 pneumonia damages alveolar type II cells and disrupts surfactant homeostasis, contributing to acute respiratory distress syndrome (ARDS). Surfactant proteins (SP-A, SP-B, SP-C, SP-D) are critical for reducing alveolar surface tension and for innate immune defense. We aimed to evaluate whether surfactant protein gene expression varies with the severity of COVID-19. Methods: Peripheral blood was collected from 122 adults with confirmed COVID-19, categorized as asymptomatic (no symptoms), mild (requiring hospitalization), or severe (requiring ICU admission). We quantified mRNA expression of surfactant protein genes (SFTPA1, SFTPA2, SFTPB, SFTPC, SFTPD) in blood cells using RT-qPCR. Relative expression was normalized to GAPDH and compared among the groups using the 2−ΔΔCt method. Outliers (Ct values > 3 SD from the mean) were excluded before analysis. Results: Distinct surfactant gene expression patterns were markedly associated with disease severity. Transcripts of SFTPB and SFTPC decreased with increasing severity of the disease. Notably, SFTPC expression was ~49-fold higher in mild cases compared to asymptomatic COVID-19-positive patients (p < 0.0001), but then decreased by ~54-fold in severe cases relative to mild (p < 0.0001), returning to near-baseline levels. In contrast, SFTPA2 and SFTPD were dramatically upregulated in severe cases. SFTPA2 was ~50-fold higher in severe versus mild cases (p < 0.0001), and SFTPD was ~4346-fold higher in severe versus asymptomatic cases (p < 0.0001; ~9.6-fold higher than in mild). SFTPA1 showed only a modest ~1.4-fold decrease in severe cases (vs. mild). All noted differences remained statistically significant after outlier exclusion. Conclusions: COVID-19 severity is correlated with profound changes in surfactant gene expression in blood. Critically ill patients exhibit loss of key surfactant components (SP-B and SP-C transcripts) alongside an excessive SP-D response. These preliminary findings suggest an imbalance that may contribute to lung injury in severe disease. However, further validation is needed to establish surfactant proteins, such as SP-D, as biomarkers of COVID-19 severity.